P300 in individuals with sensorineural hearing loss - Reis, Ana Cláudia Mirandola Barbosa; Frizzo, Ana Claudia Figueiredo [UNESP]; Isaac, Myriam De Lima; Garcia, Cristiane Fregonesi Dutra; Funayama, Carolina Araújo Rodrigues; Iório, Maria Cecília Martinelli (Associação Brasileira de Otorrinolaringologia e Cirurgia Cervicofacial, 2015)
INTRODUCTION: Behavioral and electrophysiological auditory evaluations contribute to the understanding of the auditory system and of the process of intervention. OBJECTIVE: To study P300 in subjects with severe or profound sensorineural hearing loss. METHODS: This was a descriptive cross-sectional prospective study. It included 29 individuals of both genders with severe or profound sensorineural hearing loss without other type of disorders, aged 11 to 42 years; all were assessed by behavioral audiological evaluation and auditory evoked potentials. RESULTS: A recording of the P3 wave was obtained in 17 individuals, with a mean latency of 326.97 ms and mean amplitude of 3.76 V. There were significant differences in latency in relation to age and in amplitude according to degree of hearing loss. There was a statistically significant association of the P300 results with the degrees of hearing loss (p = 0.04), with the predominant auditory communication channels (p < 0.0001), and with time of hearing loss. CONCLUSIONS: P300 can be recorded in individuals with severe and profound congenital sensorineural hearing loss; it may contribute to the understanding of cortical development and is a good predictor of the early intervention outcome.

INTRODUÇÃO: As avaliações comportamentais e eletrofisiológicas auditivas contribuem para o entendimento do sistema auditivo e do processo de intervenção. OBJETIVO: Estudar P300 em indivíduos com perda auditiva sensorioneural severa ou profunda. MÉTODO: Estudo prospectivo transversal descritivo. Participaram 29 indivíduos, de ambos os sexos, com idade entre 18 e 45 anos com perda auditiva sensorioneural, congênita severa ou profunda e sem comorbidades, avaliados por meio de avaliação audiológica comportamental e potencial evocado auditivo de longa latência. RESULTADOS: O registro da onda P3 foi obtido em 17 indivíduos, com latência e amplitude média de 326,97 ms e 3,76V, respectivamente. Houve diferenças significativas da medida de latência em relação à idade e da amplitude segundo o grau da perda auditiva. Evidenciou-se associação do resultado do P300 aos graus de perda auditiva (p = 0,04) e ao canal de comunicação auditiva predominante (p = 0,0001) e ao tempo de privação auditiva (teste exato de Fisher). CONCLUSÕES: P300 pode ser registrado em indivíduos com perda auditiva sensorioneural congênita e colaborar para a compreensão do desenvolvimento cortical auditivo e ser preditor do resultado da intervenção.
P300 em indivíduos com perda auditiva sensorioneural
Keywords: Event-related potentials, P300; Electrophysiology; Auditory evoked potentials; Hearing loss; Auditory cortex; Potencial evocado P300; Eletrofisiologia; Potenciais evocados auditivos; Perda auditiva; Córtex auditivo